Inhibition of L-NAME-induced hypertension by combined treatment with apocynin and catalase: the role of Nox 4 expression - Chia, T. Y; Murugaiyah, V; Khan, N. A. K; Sattar, M. A; Abdulla, M. H; Johns, E. J; Ahmad, A; Hassan, Z; Kaur, G; Mei, H. Y; Ahmad, F. U; Akhtar, S (Physiological research, 2021)
Reactive oxygen species (ROS) such as superoxide (O2-) generated by NAD(P)H oxidases have emerged as important molecules in blood pressure regulation. This study investigated the effect of apocynin and catalase on blood pressure and renal haemodynamic and excretory function in an L-NAME induced hypertension model. Forty Male Wistar-Kyoto (WKY) rats (n=8 per group) were treated with either: vehicle (WKY-C); L-NAME (WKY-L, 15 mg/kg/day in drinking fluid); WKY-L given apocynin to block NAD(P)H oxidase (WKY-LApo, 73 mg/kg/day in drinking water.); WKY-L given catalase to enhance ROS scavenging (WKY-LCat, 10000 U/kg/day i.p.); and WKY-L receiving apocynin plus catalase (WKY-LApoCat) daily for 14 days. L-NAME elevated systolic blood pressure (SBP), 116+/-1 to 181±4 mmHg, reduced creatinine clearance, 1.69+/-0.26 to 0.97+/-0.05 ml/min/kg and fractional sodium excretion, 0.84+/-0.09 to 0.55+/-0.09 % at day 14. Concomitantly, plasma malondialdehyde (MDA) increased six fold, while plasma total superoxide dismutase (T-SOD), plasma nitric oxide (NO) and plasma total antioxidant capacity (T-AOC) were decreased by 60-70 % and Nox 4 mRNA expression was increased 2-fold. Treatment with apocynin and catalase attenuated the increase in SBP and improved renal function, enhanced antioxidative stress capacity and reduced the magnitude of Nox4 mRNAs expression in the L-NAME treated rats. This study demonstrated that apocynin and catalase offset the development of L-NAME induced hypertension, renal dysfunction and reduced oxidative stress status, possibly contributed by a reduction in Nox4 expression during NOS inhibition. These findings would suggest that antioxidant compounds such as apocynin and catalase have potential in treating cardiovascular diseases.
Keywords: Animals; katalasa; hypertenze; Antioxidants; Catalase; NADPH-oxidasa 4; potkani inbrední WKY; Hemodynamics; hemodynamika; Enzyme Inhibitors; Reactive Oxygen Species; Rats, Inbred WKY; Hypertension; NG-Nitroarginine Methyl Ester; Male; modely nemocí na zvířatech; NG-nitroargininmethylester; inhibitory enzymů; antioxidancia; NADPH Oxidase 4; kombinovaná farmakoterapie; Disease Models, Animal; reaktivní formy kyslíku; krysa rodu Rattus; zvířata; mužské pohlaví; Acetophenones; Rats; acetofenony; Drug Therapy, Combination